Improving service delivery through partnerships between local government, civil society and the private sector : a case study of Imizamo Yethu - Matibane, Luvuyo P. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Public and Development Management))--University of Stellenbosch, 2010.